ANALISIS FAKTOR-FAKTOR PENGHAMBAT PERTUMBUHAN EKONOMI MASYARAKAT DI KAMPUNG HIRIPAU DISTRIK MIMIKA TIMUR KABUPATEN MIMIKA - Mirna .; Stepanus Sandy (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2017)
This research aims to know the inhibiting factors of the people economic growth in Hiripau village, eastern Mimika district, Mimika regency. This research was done in Mimika regency in August up to December 2014. The collecting of data was done by observation, interviews and questionnaires. The Data analyzed by factor analysis. The results of research showed that the factor of human resources factor, natural resources factor, knowledge and technologi factors, culture factors and capital are the obstacle factors of economic growth in Hiripau village, Mimika Timur district, Mimika regency.